2019
DOI: 10.12669/pjms.35.3.844
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of electrolyte imbalance in Type 2 diabetes patients: Experience from a tertiary care hospital

Abstract: Objective: To determine frequency of electrolyte imbalance including sodium, chloride, potassium and magnesium levels present in patients with uncontrolled diabetes at a tertiary care hospital in Karachi. Methods: This was a descriptive cross sectional study conducted at Medicine Department, Darul Sehat Hospital, Karachi, Pakistan from March 2017 to October 2017. A total of one hundred and eighty one admitted and OPD patients with uncontrolled diabetes (HbA1c more than 7%) were included and their demogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 16 publications
(19 reference statements)
1
12
0
Order By: Relevance
“…An increase in urea level is seen when there is damage to the kidney in the presence of high blood sugar levels in diabetic patients [18]. The statistically significant difference in serum albumin is in line with the study that had shown that serum albumin was significantly associated with the severity of retinopathy and neuropathy [28].Agoro et al showed that total protein in type 2 diabetes mellitus was decreased significantly statistically due to hypervolemia as a result of the increased osmolality of the blood caused by hyperglycemia [29].The decrease in the level of serum sodium and chloride levels in our study is in line with another study which had shown a significant reduction in serum sodium and chloride levels with an increase in fasting blood glucose levels [30].…”
Section: Discussion:-supporting
confidence: 91%
“…An increase in urea level is seen when there is damage to the kidney in the presence of high blood sugar levels in diabetic patients [18]. The statistically significant difference in serum albumin is in line with the study that had shown that serum albumin was significantly associated with the severity of retinopathy and neuropathy [28].Agoro et al showed that total protein in type 2 diabetes mellitus was decreased significantly statistically due to hypervolemia as a result of the increased osmolality of the blood caused by hyperglycemia [29].The decrease in the level of serum sodium and chloride levels in our study is in line with another study which had shown a significant reduction in serum sodium and chloride levels with an increase in fasting blood glucose levels [30].…”
Section: Discussion:-supporting
confidence: 91%
“…As shown in Figure 1 and Figure 2 both serum K + recorded insignificant correlation with duration of diabetes mellitus (R = 0.248, p = 0.08 and R = 0.045, p = 0.758 respectively) in the study group, Where as HA1C is significantly correlated with the duration of diabetes (R-= 0.425, p = 0.002) in Figure 3 In the current study mean serum level of sodium and potassium were significantly decreased in type 2 diabetes patients Which are inconsistence with the studies performed by Nabil et al 2016 [13] and Ugwuja et al (2006) [14], and disagree with Sarguru et al (2016) [15] and McDonnell et al (2005) [16] . Another studies conducted by Rashid et al 2019 [17] and Alaka and Saurabh (2016) [18] observed that Serum Na + was significantly low and serum Cl − , Ca 2+ Open Access Library Journal Table 3. Mean comparison of study parameters in male versus female in the study group.…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted on diabetic patients of Saudi Arabia, reported a significant reduction in serum sodium levels among types I or II diabetic patients especially among insulin-treated patients (12). Serum sodium level decreases as fasting blood glucose increases in diabetes mellitus and osmotic diuresis is the cause of dysnatremia (13). Thus, diabetes mellitus is associated with either hyponatremia or hypernatremia based on the hyperglycemic state, which tends to shift serum sodium to opposite directions.…”
Section: Resultsmentioning
confidence: 99%